The premium on acquisition in South African mergers: An empirical evaluation - J. F. Affleck-Graves; G. H. Burt; S. J.M. Cleasby (South African Journal of Business Management, 1988)
In this paper both the premium paid on acquisition during a merger as well as the method by which the target companies stockholders are paid for their holding are examined. The results indicate that in the South African (S.A.) context the average premium paid on acquisition is of the order of 30-40% which is approximately the same as that paid on other major exchanges. Efforts to determine those accounting and market-related variables which were highly correlated with the premium on acquisition were relatively unsuccessful with only the price/ earnings ratio (and, to a lesser extent relative size) being significantly correlated with the premium. In both cases, the correlations were positive, indicating that a higher P/E ratio in the target company and/or a target company which is large relative to the acquirer will result in a higher premium on acquisition. Finally, the results indicate that a cash payment remains the most popular method of payment in South African mergers, followed by an equity swap. These results appear to be time independent.